Discours et pratiques féministes contemporaines dans et hors des frontières - Avtar Brah; Clelia Clini (Genre, Sexualité et Société)
Avtar Brah is Professor Emerita at Birkbeck College, University of London. Her book Cartographies of a Diaspora (1996) has been widely read internationally and opened up new perspectives on ‘difference’ and ‘diversity’, informed by feminism and post-structuralism. An early advocate of intersectionality, she is also the longest standing member of the Feminist Review. In this interview, conducted in December 2016, Avtar Brah reflects on her own personal journey to academia and activism, and discusses the value of a postcolonial approach to questions of identity, migration and border crossing at times of resurgent nationalism. In particular, she addresses the value of transnational feminism and the utility of an intersectional framework of analysis to understand the so-called “refugee crisis”, the persistence of racism and sexism in contemporary culture and the state of feminism.